The correlation between nursing students’ perceptions of the nursing profession and their motivation to continue nursing professional education - Suratmi; Nurul Hikmatun Qowi; Dias Tiara Putri Utomo; Masunatul Ubudiyah (Journal of Clinical Nursing Studies and Practice, 2025)
Completing nursing professional education has become a requirement for working as a clinician in a hospital. Unfortunately, many students were not motivated to pursue nursing professional education due to their negative perceptions about the nursing profession. This study aims to determine the correlation between students’ perceptions of the nursing profession and their motivation to continue nursing professional education in the eighth semester at Universitas Muhammadiyah Lamongan. This study employed a cross-sectional design, utilizing a simple random sampling technique, which yielded 114 respondents. This study was conducted in February 2020. The independent variable was students’ perceptions of the nursing profession, and the dependent variable was students’ motivation to continue nursing professional education. The instrument used for both variables was a closed questionnaire. The data was analyzed univariately and bivariately. The Spearman’s rank correlation test was used for bivariate analysis. The results indicated that the majority of students’ perceptions fell into the good category (71 students, 62.3%), while the motivation was categorized as moderate (59 students, 51.8%). On the other hand, Spearman’s rank correlation test yielded a p-value of 0.000, indicating a significant correlation between students’ perceptions of the nursing profession and their motivation to pursue nursing professional education. Based on the results of this study, it is hoped that students will gain a deeper understanding of the nursing profession by seeking practical experience and participating in training, thereby becoming more motivated to continue their nursing education.